2021
DOI: 10.1101/2021.05.31.445806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The neurogenic fate of the hindbrain boundaries relies on Notch-dependent asymmetric cell divisions

Abstract: The generation of cell diversity in the central nervous system occurs during embryogenesis and requires a precise balance between stem cell proliferation, neuronal commitment to specific fates, and further differentiation. Understanding the cellular and molecular mechanisms regulating this balance in the embryonic brain is challenging. Here we reveal how the neurogenic capacity in the hindbrain is differently allocated to distinct domains over time, and how the boundary cells undergo a functional transition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…Moreover, such studies have demonstrated that individual neural progenitor undergo probabilistic and deterministic decisions in generating neuron and glial cell diversity (Gao et al, 2014;Llorca et al, 2019). Similar studies have been performed in zebrafish hindbrain and retina to elucidate the rules and molecular regulators governing NPC lineage decisions and how NPC competence to generate diverse cell types changes as development proceeds (Boije et al, 2015;Hevia et al, 2021;Nerli et al, 2022;Zhao et al, 2021). Moreover, studies using live imaging microscopy can provide valuable insights into the mechanisms underlying asymmetric versus symmetric division modes (Clark et al, 2021;Kressmann et al, 2015;Nerli et al, 2020).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Moreover, such studies have demonstrated that individual neural progenitor undergo probabilistic and deterministic decisions in generating neuron and glial cell diversity (Gao et al, 2014;Llorca et al, 2019). Similar studies have been performed in zebrafish hindbrain and retina to elucidate the rules and molecular regulators governing NPC lineage decisions and how NPC competence to generate diverse cell types changes as development proceeds (Boije et al, 2015;Hevia et al, 2021;Nerli et al, 2022;Zhao et al, 2021). Moreover, studies using live imaging microscopy can provide valuable insights into the mechanisms underlying asymmetric versus symmetric division modes (Clark et al, 2021;Kressmann et al, 2015;Nerli et al, 2020).…”
Section: Discussionmentioning
confidence: 84%
“…described for areas of the zebrafish nervous system such as the hindbrain, spinal cord and retina (Boije et al, 2015;He et al, 2012;Hevia et al, 2021;Kimura et al, 2008;Nerli et al, 2022;Satou et al, 2012). In this experimental work, we extend the existing body of work with an quantitative characterization of the first wave of neurogenesis in the developing zebrafish telencephalon using machine-learning based nuclear segmentation and clonal analysis methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the zebrafish and rat retina, tracking of individual clones through time-lapse imaging with cell fate markers shows high variability in the clonal size and composition of the lineages generated by individual NPCs ( Figure 1G , Gomes et al, 2011 ; He et al, 2012 ). Similarly, live imaging of NPCs in the developing zebrafish telencephalon and hindbrain show heterogeneity in the NPC division modes present at neurogenic stages ( Dong et al, 2012 ; Hevia et al, 2021 ). Intriguingly, in the zebrafish retina, the probabilities for retinal NPCs to undergo P-P, P-N or N-N divisions change over time ( Figure 1G ).…”
Section: Stochasticity Versus Determinism In Division Mode Selection ...mentioning
confidence: 99%
“…This morphogenetic process is accompanied with the initial neuronal differentiation, which starts prior 24 hours post-fertilization (hpf) with a pronounced increase from 30 hpf onwards (Voltes et al, 2019). Neuronal differentiation involves changes in cell proliferative capacity and an extraordinary displacement of neurons from their birth site, and occurs while other dramatic changes take place, such as the generation of the brain ventricle (Belzunce et al, 2020; Gutzman et al, 2008; Hevia et al, 2021; Lyons et al, 2003). Although previous work evoked the importance of the order of neuronal differentiation in ascribing final neuronal position within specific circuits (Kinkhabwala et al, 2011; Pujala and Koyama, 2019; Wan et al, 2019), little is known about the role of the neuronal birthdate in the final organization of differentiated neurons within the hindbrain.…”
Section: Introductionmentioning
confidence: 99%